Nutritional Improvements of Sourdough Breads Made with Freeze-Dried Functional Adjuncts Based on Probiotic Lactiplantibacillus plantarum subsp. plantarum and Pomegranate Juice - Stavros Plessas; Ioanna Mantzourani; Athanasios Alexopoulos; Maria Alexandri; Nikolaos Kopsahelis; Vasiliki Adamopoulou; Argyro Bekatorou (MDPI AG, 2023)
New types of sourdough breads are proposed, made with freeze-dried sourdough adjuncts based on: (i) Lactiplantibacillus plantarum subsp. plantarum ATCC 14917, a potential probiotic (LP) alone or (ii) with the addition of unfermented pomegranate juice (LPPO) and (iii) pomegranate juice fermented by the same strain (POLP). Physicochemical, microbiological, and nutritional characteristics (in vitro antioxidant capacity, AC, total phenolics, TPC, and phytate content) of the breads were evaluated and compared with commercial sourdough bread. All adjuncts performed well; the best results being those obtained by POLP. Specifically, the highest acidity (9.95 mL of 0.1 M NaOH) and organic acid content (3.02 and 0.95 g/kg, lactic and acetic acid, respectively) as well as better resistance to mold and rope spoilage (12 and 13 days, respectively) were observed for POLP3 bread (sourdough with 6% POLP). Significant nutritional improvements were observed by all adjuncts, in terms of TPC, AC, and phytate reduction (103 mg gallic acid/100 g, 232 mg Trolox/100 g, and 90.2%, respectively, for POLP3). In all cases, the higher the amount of adjunct, the better the results. Finally, the good sensory properties of the products indicate the suitability of the proposed adjuncts for sourdough breadmaking, while their application in freeze-dried, powdered form can facilitate commercial application.